The (Lack of) DNA Double-Strand Break Repair Pathway Choice During V(D)J Recombination - Libri, Alice; Marton, Timea; Deriano, Ludovic (Frontiers in Genetics, 2022)
DNA double-strand breaks (DSBs) are highly toxic lesions that can be mended via several DNA repair pathways. Multiple factors can influence the choice and the restrictiveness of repair towards a given pathway in order to warrant the maintenance of genome integrity. During V(D)J recombination, RAG-induced DSBs are (almost) exclusively repaired by the non-homologous end-joining (NHEJ) pathway for the benefit of antigen receptor gene diversity. Here, we review the various parameters that constrain repair of RAG-generated DSBs to NHEJ, including the peculiarity of DNA DSB ends generated by the RAG nuclease, the establishment and maintenance of a post-cleavage synaptic complex, and the protection of DNA ends against resection and (micro)homology-directed repair. In this physiological context, we highlight that certain DSBs have limited DNA repair pathway choice options.